If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 1) = 10 Reorder the terms: 5(1 + 2x) = 10 (1 * 5 + 2x * 5) = 10 (5 + 10x) = 10 Solving 5 + 10x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 10x = 10 + -5 Combine like terms: 5 + -5 = 0 0 + 10x = 10 + -5 10x = 10 + -5 Combine like terms: 10 + -5 = 5 10x = 5 Divide each side by '10'. x = 0.5 Simplifying x = 0.5
| 13x-4=12x-1 | | P=2l+2wfore | | 26=6(5-4*.1666666667) | | 15x-9=10x+1 | | 6(x*x)-19x-7= | | 4.2q-5.7-5.3q=-0.1q-5.7 | | -13+n=-2 | | 3k-2(-5k-4)=2+3(5k-8) | | 12x+2=11x+5 | | 4(x*x)+9x+5= | | 12x=22+x | | 6x+4/2 | | t^2-t/2-10 | | 7-y/4=9 | | 9/9=72 | | x^2+70x-32100=0 | | 13yrd=inch | | 7p+8=6p+5 | | 2x^2-4x+7=1 | | x*x-6x-27= | | 1/3x/8=10 | | 5(-1)+2y=8 | | 26=6(30-24f) | | 13yrd= | | x*x-11x+24= | | 2a^3+10a^2= | | y*=77 | | -15n+3n= | | -16t^2+44t+180=0 | | 23(x/8)=10 | | 12=-2(-9-3x) | | x*x+5x-6= |